KEEFEKTIFAN MODEL PENDIDIKAN BUDI PEKERTI BERBASIS CERITA ANAK MELALUI PENANAMAN NILAI ETIS-SPIRITUAL SISWA SD - Edy Suryanto; Raheni Suhita Raheni Suhita; Yant Mujiyanto Yant Mujiyanto (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2014)
Abstract: Effectiveness of moral education on the basis of children story through ethic-spiritual value transformation elementary school’s students. Purpose of the research was to produce moral education for elementary schools’ students and to test effectiveness of moral education model for elementary schools’ students. Research method was descriptive qualitative. Data collection techniques were observation, interview, document analysis, and test. Data analysis used interactive model, while testing used experiment technique. Research results; (1) Developing moral education model based on children story packed until step students finding value through questions and internalization process through role-play, The meaningfulness of moral education if followed with habituation on other relevant subjects, modeling, and figure model; and (2) Model can be used as an ethic spiritual value character transformation of elementary schools’ students.Keywords: moral, children story, ethic spiritual value, elementary schools’ students Abstrak: Penelitian ini bertujuan: menghasilkan model pendidikan budi pekerti untuk siswa SD dan menguji keefektifan model pendidikan budi pekerti untuk siswa SD. Metode penelitian deskriptif kualitatif. Teknik pengumpulan data dengan cara observasi, wawancara, analisis dokumen, dan tes. Analisis data menggunakan model interaktif, sedangkan pengujian dengan teknik eksperimen. Hasil penelitian:(1) pengembangan model pendidikan budi pekerti berbasis cerita anak dikemas sampai pada tahap siswa menemukan nilai melalui pertanyaan-pertanyaan dan proses internalisasi melalui bermain peran. Kebermaknaan pendidikan budi pekerti bila ditindaklanjuti dengan pembiasaan pada mata pelajaran lain yang relevan, pemodelan, dan keteladanan; dan (2) Model dapat digunakan untuk penanaman karakter nilai etis spiritual siswa SD.Kata Kunci: budi pekerti, cerita anak, nilai etis-spiritual, siswa SD